A Critical Analysis of the Relationship between"Meta-Philosophy" and "Methodology"A Critique on the Book The End of the Philosophy of Religion - Malek Shojaijashughani; Fatemeh Bozorgzade (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Nick Trakakis, the contemporary philosopher of religion, in his book The End of the Philosophy of Religion, presents his idea on the relationship between metaphilosophy and methodology of the contemporary philosophy of religion in both analytical and continental traditions. Before entering into the controversial debates and issues of the philosophy of religion, he tries to understand the methods and goals pursued in the philosophical traditions, as well as to analyze and critique the strengths and weaknesses of these traditions. To achieve the above goal, Trakakis deals with the design and formulation of the distinction and similarity of philosophical styles in the two analytical and continental traditions. Trakakis examines the examples of thinkers from these two traditions and concludes that the religious philosophy in the analytical tradition seeks to assume a particular point of view in metaphilosophy and philosophical methodology, within the narrow confines on scientifically rationalized and logical arguments - independent of the concrete and existential concerns of human life. While introducing analytical key themes in his book The End of the Philosophy of Religion, this paper critique the Trakakis 's views from a methodological point of view and its relationship to metaphilosoph.